2005
DOI: 10.1038/ncb1263
|View full text |Cite
|
Sign up to set email alerts
|

Crm1 is a mitotic effector of Ran-GTP in somatic cells

Abstract: The Ran GTPase controls multiple cellular processes, including nuclear transport, mitotic checkpoints, spindle assembly and post-mitotic nuclear envelope reassembly. Here we examine the mitotic function of Crm1, the Ran-GTP-binding nuclear export receptor for leucine-rich cargo (bearing nuclear export sequence) and Snurportin-1 (ref. 3). We find that Crm1 localizes to kinetochores, and that Crm1 ternary complex assembly is essential for Ran-GTP-dependent recruitment of Ran GTPase-activating protein 1 (Ran-GAP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
209
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(230 citation statements)
references
References 29 publications
11
209
0
2
Order By: Relevance
“…The functional consequences of the nucleocytoplasmic shuttling of Survivin and Aurora B before NEB remain to be established. However, it has been recently reported that, besides its function as a nuclear export receptor, CRM1 has a role determining the localization of proteins to chromosome kinetochores during mitosis (Arnaoutov et al, 2005). In this respect, our initial experiments demonstrate that extended LMB treatment disrupts the localization of endogenous Survivin and Aurora B to the centromeric region of prophase and (pro)metaphase cells.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The functional consequences of the nucleocytoplasmic shuttling of Survivin and Aurora B before NEB remain to be established. However, it has been recently reported that, besides its function as a nuclear export receptor, CRM1 has a role determining the localization of proteins to chromosome kinetochores during mitosis (Arnaoutov et al, 2005). In this respect, our initial experiments demonstrate that extended LMB treatment disrupts the localization of endogenous Survivin and Aurora B to the centromeric region of prophase and (pro)metaphase cells.…”
Section: Discussionmentioning
confidence: 60%
“…In this respect, our initial experiments demonstrate that extended LMB treatment disrupts the localization of endogenous Survivin and Aurora B to the centromeric region of prophase and (pro)metaphase cells. We show that, unlike that of RanBP2 (Arnaoutov et al, 2005), the localization of the CPPs is only disrupted after sustained blockage of CRM1 activity, suggesting that the presence of LMB during the preceding interphase may contribute to the observed effect. Therefore, further experimental evidence is needed to clarify the relationship between the CRM1 pathway and the CPPs during mitosis.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…3, 5 and 6). It is attractive to speculate that such regulation could be mechanistically related to Nup358Õs function at mitotic kinetochores [6][7][8]. In this case, it will be of considerable interest to determine how the Ran GTPase may be involved in Nup358Õs control of interphase microtubule dynamics.…”
Section: Nup358mentioning
confidence: 99%